The Effect of Peer Tutoring with Project-Based Learning Model on Educational Statistics Course - Oktaviana Ainun Ratnawati; Wahyu Nugroho; Emy Artuti (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2026)
This study investigates the effect of combining peer tutoring with a project-based learning (PjBL) model on the academic performance of students enrolled in an Educational Statistics course within an elementary teacher education program. A quasi-experimental design was employed with two intact classes (n = 42) from a state university in Indonesia. The experimental group received peer-assisted PjBL instruction, while the control group experienced conventional PjBL without peer tutors. Both groups followed the same syllabus, instructor, and assessment structure. Data were collected through standardized Midterm (UTS) and Final (UAS) exams validated by subject-matter experts. The findings revealed that students in the experimental group achieved significantly higher academic performance and demonstrated greater improvement from midterm to final exams compared to the control group, with a moderate effect size (Cohen’s d = 0.59). The integration of peer tutoring within project-based activities effectively reduced anxiety, encouraged collaboration, and deepened conceptual understanding of statistical principles. These results confirm that peer-supported, project-based instruction offers a practical and contextually relevant approach to improving statistical learning outcomes among pre-service teachers. The study underscores the importance of active, student-centered pedagogies in preparing future educators to navigate data-rich educational environments. Future research is recommended to examine the long-term retention, scalability, and adaptation of this model across different subjects and institutional settings.